APLIKASI VIDEO CONFERENCE SEBAGAI MEDIA PEMBELAJARAN DARING MASA PANDEMI COVID-19 DI PRODI PENDIDIKAN ADMINISTRASI PERKANTORAN - Firdausa Hulif Fuada; Hery Sawiji; Winarno Winarno (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
Abstract This study aimed to determine the use of video conference applications as online learning media during the Covid-19 pandemic in the Office Administration Education Study Program, the obstacles that occurred and solutions of the problem. This study used a descriptive qualitative method with a case study approach. The data sources of this study included interviewees, locations and events, and documents.The research sampling techniques used were purposive sampling and snowball sampling techniques. Whereas the data collection techniques used were triangulation technique and interviewees triangulation. The data analysis technique used was interactive analysis the research results, it shows thatthe use of video conference applications as online learning media is one of the alternatives to support the online learning process during the Covid-19 were easy to use and could be used to overcome the limitations in space and time. The obstacles experienced while using video conference applications as learning media are limited quotas, unstable internet connection, and an inconducive learning environment. The solutions taken to overcome the obstacles experienced are utilizing the quotas provided by the government, using a good Wi-Fi or provider in the area where each student lives, and creating a conducive learning environment while using video conference applications.